Nacht und Gerechtigkeit - die Stadtnacht als spezifischer Zeit-Raum - Charlotte Weber; Dietrich Henckel (Zeitgerechte Stadt: Konzepte und Perspektiven für die Planungspraxis, 2019)
Die Eroberung der Stadtnacht ist an die Verfügbarkeit der künstlichen Beleuchtung gebunden und erfolgte daher menschheitsgeschichtlich sehr spät. Stadtnacht wird trotz aller Erschließung - die allerdings weit von 24/7 entfernt ist - weiterhin als "anderer" Zeit-Raum wahrgenommen. Zum einen ist Dunkelheit nach wie vor mit negativen Assoziationen behaftet, zum anderen scheint Nacht als Kapazitätsreserve, als Raum für Freiheit, Kreativität und Experiment, der andere Möglichkeiten als der Tag eröffnet. Gleichzeitig steigen durch die zeitliche Ausdehnung von Aktivitäten in die Nacht hinein auch ökonomische Potenziale der Nachtnutzung, Nacht gewinnt als Wirtschaftsfaktor an Bedeutung. Damit sind in besonderem Maße unterschiedliche Vorstellungen, Normen und Ansprüche zur wünschenswerten, zulässigen, akzeptablen Nutzung der Stadtnacht verbunden, mit der Folge hoher Konfliktpotenziale und Konfliktintensität, die Fragen der Zeitgerechtigkeit in der Stadtnacht aufwerfen. Wer sind die Akteure der Kolonisierung der Stadtnacht? Welche Konsequenzen ergeben sich und wie sind die Folgen räumlich, zeitlich und sozial verteilt? Wenn es um die freiwillige Nutzung der Stadtnacht geht, ergeben sich darüber hinaus Fragen, ob die Erschließung der Stadtnacht für alle gleichermaßen erfolgt oder ob es spezifische raumzeitliche Selektivitäten gibt. Gerade im Zusammenhang mit dem Wachstum der nächtlichen Vergnügungswirtschaft und der nächtlichen Erschließung durch den öffentlichen Nahverkehr rücken Konflikte zunehmend auch ins öffentliche Bewusstsein, werden Teil einer öffentlichen Debatte um Stadtnacht. Diese Konflikte und der Umgang mit planerischen Steuerungs- und Interventionsmöglichkeiten spielen eine zentrale Rolle für die Auseinandersetzung mit Fragen der raumzeitlichen Gerechtigkeit in der Stadtnacht und stehen daher im Zentrum dieses Beitrages. – – Since the availability of artificial light, it has been possible to observe a stepwise conquest of the urban night through the temporal expansion of activities and offerings. The extension of production hours and the increasing flexibility of working hours, the growing proportion of night work and corresponding changes in the availability of services, infrastructure and public transport, in addition to growth in the night-time entertainment industry have led to the colonisation of urban evenings and nights. Alongside critical investigations of, for instance, the adverse health effects of night work, the positive connotations of the "city that never sleeps" are increasingly prominent. The urban night is gaining significance as an economic factor due to the potential it offers for an expansion of economic activities. Furthermore, in the context of neoliberal competition between cities, a lively urban nightlife is increasingly viewed as an important competitive factor for the attraction and long-term retention of visitors, inhabitants and firms. The opening up of the urban night is not a uniform process but one that is spatially selective. It is therefore not possible to define one urban night, but must rather be assumed that there are different, sometimes individually experienced levels of the urban night - in different cities but also within one city. This results in the emergence of a diverse nocturnal structure of use in which different imaginations, standards, expectations and demands concerning the desired, permissible and acceptable use of the urban night exist. The consequence, particularly in dense and mixed-use districts, is the emergence of a great potential for conflict and a growing number of disputes about the urban night, which raise questions of temporal justice. In addition to concrete conflicts about night work, noise, rubbish, alcohol, drugs, criminality, safety, displacement, control and surveillance, the issue of access to the urban night is of significance - both in terms of possible access to its present features and in terms of access to opportunities to participate in the negotiation and design of the nocturnal city and its (public) spaces. This paper therefore argues that the urban night requires a continuous, situational balancing of the differing, often subjective perceptions of conflict situations and ideal concepts of use, with the aim of identifying inequalities, offering trade-offs and balancing consequences so as to move towards a fair situation.
urn:nbn:de:0156-0877063; hdl:10419/194288; https://econpapers.repec.org/RePEc:zbw:arlfob:09
Keywords: 710; Stadtnacht; Nacht; Stadt- und Raumplanung; Gesellschaftsentwicklung; Recht auf Stadt; Stadtmarketing; Night-Time Economy; 24/7; Urban night; night; spatial planning; development of society; right to the city; city marketing; night-time economy